Topics in bubble nucleation - Chen, Yilin. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Physics.; Advisors: Lawrence Ford, and Alexander Vilenkin.; Committee: Ken Olum, Mark Hertzberg, Jaume Garriga, and Anthony Mann.; Keyword: Physics.